Evaluation of the Pharmaceutical theses of the government Universities of Tehran and Shahid Beheshti based on ISO 7144 during 2008 to 2012 - Kazerani, Maryam; Malgard, Shiva; Shekofteh, Maryam; Zaeri, Farid; Khadembashi, Naghmeh (Archives of Advances in Biosciences, 2016)
University theses and dissertations are among those credible sources of information which, with regard to their given status of value, and the use of update resources using the international regulations and standards, can be perfect sources for optimal recovery of information and can increase the scientific credibility. This study reviews the accordance of the Pharmaceutical theses of Shahid Beheshti University of Medical Sciences and the University of Tehran with the ISO 7144 standards: 2008-2012. 765 pharmaceutical theses of Shahid Beheshti University of Medical Sciences and the University of Tehran at both general and specialized levels were studied, using an analytical method. Data collection was based on the checklist prepared according to ISO 7144 standards. The comparisons were performed based on the t-test, using SPSS software. The results manifested that the theses done at Shahid Beheshti University of Medical Sciences adhered more to the ISO standards compared to the University of Tehran. The study also revealed that the mean score of the adherence to the standards of ISO has been more in specialized theses than the general ones. Moreover, it suggests that, due to their scientific and practical nature, theses are among the most important sources, and therefore, the manner through which the data is inserted, is of utmost importance. The accordance of the studied theses of both general and specialized themes in both universities to ISO 7144 standards is below the %50 of the desired standard and has a long way to go to reach the desired status.